(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Power abilities are an important component of success in achieving high results in modern sports. Strength training is also used in fitness programs to support general health. The study of adaptive processes in response to force loads is important for the development of recommendations for safe and effective training programs. The ability to adapt and perform ever-increasing physical loads (PhL) is provided by all functional systems of the body, the main link of which is the cardiovascular system (CVS). In this regard, the aim of this study was to find out the mechanisms of adaptation of the cardiovascular system to repeated local dynamic force loads based on the analysis of changes in cardiohemodynamics in weightlifters who specialize in strength endurance training. Material and methods. In 15 highly qualified weightlifters, parameters of central hemodynamics (CHD), as well as indicators of functional reserves of the heart and vegetative status were studied after performing three sets of local force PhL (25% of the maximum voluntary force) "to failure" and during the recovery period (at 5 and 10 minutes ). The results. The analysis of changes in cardiohemodynamics in weightlifters in response to repeated local dynamic force loads showed that even for highly qualified athletes, three sets of strength exercises "to failure" with a rest of 1 min were excessive. They caused increased activation of the mechanisms of adaptation of the cardiovascular system and indicated signs of overstrain in the work of the heart. Processes of heart overexertion were signaled by a significant increase in cardiac output, a sharp decrease in pulse arterial pressure, a significant increase in the power of the left ventricle, as well as the speed of blood expulsion and energy expenditure for moving liters of blood. These indicators changed dramatically after the third PhL (p < 0.05). In addition, parameters were found that indicated the inadequacy of the PhL to functional capabilities. These included indicators of functional reserves of the cardiovascular system, which increased sharply after the third PhL (p < 0.01), such as: average arterial pressure (AP aver), which indicated fatigue; Endurance factor (ED), which indicated weakening of the heart; Robinson’s index (IR), which indicated the weakening of the pumping function of the heart. Conclusions. The study of the processes of the reaction of the cardiovascular system to repeated local strength loads "to failure" in trained weightlifters and the detection of CHD indicators, which indicate cardiac overstrain, will allow a better understanding of the mechanisms of adaptation of the cardiovascular system to strength training. It will also help in the dosage of PhL to optimize training programs in order to improve the results and preserve the health of athletes, as well as people who use strength loads in fitness programs.